Handheld Active Add-On Control Unit for a Cable-Driven Flexible Endoscope - Legrand, Julie; Javaux, Allan; Ourak, Mouloud; Wenmakers, Dirk; Vercauteren, Tom; Deprest, Jan; Ourselin, Sebastien; Denis, Kathleen; Vander Poorten, Emmanuel (Frontiers in Robotics and AI, 2019)
The instruments currently used by surgeons for in utero treatment of the twin-to-twin transfusion syndrome (TTTS) are rigid or semi-rigid. Their poor dexterity makes this surgical intervention risky and the surgeon's work very complex. This paper proposes the design, assembly and quantitative evaluation of an add-on system intended to be placed on a commercialized cable-driven flexible endoscope. The add-on system is lightweight and easily exchangeable thanks to the McKibben muscle actuators embedded in its system. The combination of the flexible endoscope and the new add-on unit results in an easy controllable flexible instrument with great potential use in TTTS treatment, and especially for regions that are hard to reach with conventional instruments. The fetoscope has a precision of 7.4% over its entire bending range and allows to decrease the maximum planar force on the body wall of 6.15% compared to the original endoscope. The add-on control system also allows a more stable and precise actuation of the endoscope flexible tip.